Symmetries in intermediate and high energy physics - Faessler, A. (Springer tracts in modern physics, 2000)
This book contains comprehensive reviews of modern topics in nuclear physics, particle physics, astrophysics and cosmology. Special emphasis is put on the role of several symmetries in physics at intermediate and high energies and on neutrino physics, with its implications in nuclear astrophysics and cosmology. Many applications of the theories and experiments are included, along with interesting information on recent developments with respect to current problems in modern physics. The book is therefore especially useful to new scientists and graduate students.